Bayi Baru Lahir dengan Kelainan Kongenital berupa Menigoensefalokel Parietal: Sebuah Laporan Kasus - Arninda Rahman; Danny Yovita Maharani; Nurul Islamy; Javedh Iqbal (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Meningoencephalocele is a rare congenital disorder with an incidence of 1–4 cases per 10,000 live births. Meningoencephalocele is a congenital abnormality resulting from a neural tube defect. The male patient was born at term with cesarean section on indication of congenital abnormalities. The patient had a lump on the side of the head since birth. The patient's mother admitted that she did not consume enough folic acid during pregnancy. On physical examination found a lump in the occipital with a size of 15x15 cm. No blood or pus was found. There is a fluctuation and indicates a transillumination. A CT scan of the head without contrast revealed a parietal meningoencephalocele with a regional defect. The patient was given management in the form of a mass dressing with sterile gauze/24 hours, antibiotics, analgesics and meeting the patient's fluid needs. The patient underwent neurosurgical surgery, namely resection of transcranial meningoencephalocele followed by careful observation and monitoring of the baby's vital signs during surgery. After surgery, there was no evidence of cerebrospinal infection and leakage of cerebrospinal fluid. The wound healed completely and there was no sign of increased intracranial pressure during hospitalization. Head circumference was measured and graphed twice a week. The patient's condition was followed up and showed improvement every day. The research method used an empirical case study that investigated a symptom in a real-life setting and it was concluded that the patient had no visible involvement of the brain in the parietal meningoencephalocele and no hydrocephalus, so this patient had a good prognosis. Suggestions for further research is to look at the prognosis and complications in patients so that they can be assessed early and become a doctor's consideration in determining the action to be taken.